Factors Affecting Vascular Complications in Patients with Diabetes Mellitus: A Literature Review - Widaningsih, Ida; Ibrahim, Kusman; Nursiswati, Nursiswati (Journal of Health and Nutrition Research, 2025)
Vascular complications in patients with diabetes mellitus (DM) are a major cause of morbidity and mortality, presenting a considerable impact on quality of life and global health burden. Although diabetes management continues to improve, vascular complications remain a major challenge. It is important to understand the factors that influence these complications to support more effective prevention and management. To explore the factors influencing vascular complications in patients with DM. This study used a literature review method. Articles were searched through three major databases, namely CINAHL, PubMed, and Scopus, using keywords such as "vascular complications," "DM," and "factors affecting." Inclusion criteria included English-language articles published within the last ten years (2016–2025), in the form of original research relevant to vascular complications in patients with DM. Data were extracted manually using a table that included authors, objectives, design, samples, variables, and outcomes. Analysis was conducted using a qualitative descriptive approach to identify key themes. A total of 14 articles met the inclusion criteria. From the analysis, six main themes were obtained: biochemical factors and biomarkers, clinical factors, cardiometabolic risk factors, vascular structural and anatomical changes, molecular mechanisms, and prevalence of vascular complications. The results showed that high HbA1c levels, hypertension, diabetes duration of more than 10 years, and increased biomarkers such as Bisphenol A (BPA) significantly increased the risk of vascular complications. Vascular complications in patients with DM are multifactorial, involving complex interactions between biochemical, clinical, and molecular factors.